Conceptual framework of edutainment animated series for children: A pious story - Wan Malini, Wan Isa; Mat Atar, Mat Amin; Azilawati, Rozaimee (Asian Research Publishing Network, 2015)
The objective of this study was to develop a conceptual framework for edutainment animated series for children taking into consideration a pious story. The conceptual framework has been designed and considered as the first step to ensure attainment of the edutainment animated series. Nowadays, multimedia technology plays an important role to deliver the desired information. Animation is one of the ways used to educate children. Most animations have been brought in which implicitly deliver negative values such as violence and aggressiveness. Due to this factor, local animated series is crucial to be produced to suit with the local moral values. The pious story has been selected and designed to provide the children with the good moral values to be practiced by a good Muslim. Expert review has been conducted with two experts to validate the component in the conceptual framework. The instrument used is questionnaire with 5.00 point Likert scale. The result shows the elements in the conceptual framework are successfully implemented with overall means are above 4.00 of Likert Scale score. The designed framework could be serving as a catalyst to promote good moral value for animated series which could be used worldwide to develop Islamic edutainment.